2013
DOI: 10.5812/aapm.10242
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Application of Pulsed Radiofrequency–4 Case Reports

Abstract: It has been suggested that PRF might possibly have an effect on the immune cells. We considered using the intravenous route to apply PRF in conditions that are caused by an unresolved immune action or connected to allostatic load, implicating an abnormally reacting immune system to obtain a systemic effect that could possibly be an additional tool in treating some of these conditions. These manuscript reports four cases that illustrate the wide variety of conditions where this new technique might be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The duration of pain relief was much longer than would have been expected from steroid injections according to the literature. We therefore recommend that further research comparing the effects of this method to a control series be undertaken.We have postulated that the effect of intra-articular PRF is caused by the exposure of immune cells to low-strength RF fields ( 31 , 32 ). We recommend that PRF not be combined with steroid infiltration until the exact nature of this mechanism has been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of pain relief was much longer than would have been expected from steroid injections according to the literature. We therefore recommend that further research comparing the effects of this method to a control series be undertaken.We have postulated that the effect of intra-articular PRF is caused by the exposure of immune cells to low-strength RF fields ( 31 , 32 ). We recommend that PRF not be combined with steroid infiltration until the exact nature of this mechanism has been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system came into focus, suggesting that PRF could possibly influence the nociceptive process itself. An initial report on a second invention by Teixeira is published in this issue ( 3 ). Its background follows from his invention of intra-articular PRF.…”
mentioning
confidence: 99%
“…PRF is not limited to targeting afferent nerves, which was observed after the use of intra-articular PRF, and, as a result, it was verified that PRF promotes an analgesic effect. Therefore, it was suggested that PRF could present a local anti-inflammatory effect due to an effect on the immune system, which may ultimately impact the nociceptive process [ 22 , 23 ].…”
Section: Pulsed Radiofrequency: Mechanisms Of Actionmentioning
confidence: 99%
“…This may explain the mechanisms of long-term pain mitigation after using PRF [ 24 ]. Given its ability to impact immune cells, there are case reports considering the intravenous route to apply RF in order to treat unresolved immune issues [ 22 ].…”
Section: Pulsed Radiofrequency: Mechanisms Of Actionmentioning
confidence: 99%